In vivo imaging in an ABSL-3 regional biocontainment laboratory. Issue 2 (1st July 2014) - Scanga, Charles A.; Lopresti, Brian J.; Tomko, Jaime; Frye, Lonnie J.; Coleman, Teresa M.; Fillmore, Daniel; Carney, Jonathan P.; Lin, Philana L.; Flynn, JoAnne L.; Gardner, Christina L.; Sun, Chengqun; Klimstra, William B.; et al.
Abstract: The Regional Biocontainment Laboratory (RBL) at the University of Pittsburgh is a state of the art ABSL 3 facility that supports research on highly pathogenic viruses and bacteria. Recent advances in radiologic imaging provide several noninvasive, in vivo imaging modalities that can be used to longitudinally monitor animals following experimental infection or vaccination. The University of Pittsburgh RBL provides digital radiography, bioluminescence imaging, and PET/CT. Operating these platforms in an ABSL 3 poses unique challenges. This review will discuss the development and refinement of these imaging platforms in high containment, emphasizing specific challenges and how they were overcome. Abstract : In vivo imaging of highly pathogenic viruses and bacteria allow for real time evaluation of disease progression and treatment without the need for serial sacrifice, an advancement in the development of novel vaccines and therapeutics modalities. Abstract :